Proposta para o ensino de frações para o 7 ano: do diagnóstico à aprendizagem mediada por Modelo de Barras - Cintra, Camila Coppi (2017)
This research aims to present and analyze the contributions of the Singapore's Mathematical Bars on the fraction teaching with a focus on problem-solving. This methodology was applied to a 7th-year middle school class in a public school of São Paulo State. The motivation for this study relies on the low rate of correctness observed in the São Paulo State's unified test regarding the fraction subject, as well as on the importance of this subject in an effective transition to algebra. The Singapore's Mathematical Bars methodology was adopted because it enables a pictorial visualization, building a bridge between concrete and abstract, being particularly suitable for approaching the part-whole relations and comparison matters. The proposed activities were based on the Singapore's book "My Pals Are Here!" and cover basic fraction concepts such as numerator and denominator, obtainment of equivalent fractions, and addition and subtraction fraction operators with both equal and distinct denominators. The analysis of the results obtained in the classroom is intended to serve as a complementary material for professors which face similar teaching problems.